Plankton and contour algal communities in the ukrainian section of the Western Bug River and its tributaries: Report 1. Abiotic variables, taxonomic, ecological characteristics and floristics specifics of phytoplankton, microphytobenthos, phytoperiphyton - Shcherbak, V.I.; Semeniuk, N.Ye.; Davydov, O.A.; Koziychuk, E.Sh. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2024)
The taxonomic diversity of algae in the Western Bug River and its tributaries during the low-water summer-autumn season comprised 303 species (318 intraspecies taxa, ist) from 131 genera, 74 families, 45 orders, 16 classes and 8 phyla. Bacillariophyta dominated, Chlorophyta were recorded as subdominants. The phytoplankton taxonomic diversity included 140 ist, microphytobenthos – 191, phytoperiphyton – 172. The floristic nucleus of algal communities was formed by 17 families. In phytoplankton the highest rank belonged to Scenedesmaceae, while in contour algal communities – Naviculaceae. The highest floristic similarity was observed for microphytobenthos and phytoperiphyton, and the highest dissimilarity – for phytoplankton and phytoperiphyton. The spatial differentiation between contour and plankton communities during the low-water period, rather high similarity of their floristic structure indicate the unity of structural organization of algae from different ecological groups as an important component of biodiversity in the transboundary rivers. According to geographic distribution cosmopolites dominated; according to flow and oxygen regime – indifferents; according to pH preference – alkaliphilic and indifferent species; according to salinity preference – indifferent species; according to saprobiological characteristics – χ-ο- and β-mesosaprobic species. According to biotopic preference eurytopic and benthic forms prevailed. The dialectic unity between contour algal communities and phytoplankton to a great extent depends on morphometric and hydrological characteristics of the rivers under study. High taxonomic diversity, clearly marked spatial differentiation between planktonic and contour communities, interesting species of Bacillariophyta – all these features are indicative of the uniqueness and importance of algae in forming the biodiversity of the transboundary Western Bug River and its tributaries as the components of the EU hydrological network.